2008
DOI: 10.1534/genetics.107.084418
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent Selection and the Evolution of Assortative Mating

Abstract: A long-standing goal in evolutionary biology is to identify the conditions that promote the evolution of reproductive isolation and speciation. The factors promoting sympatric speciation have been of particular interest, both because it is notoriously difficult to prove empirically and because theoretical models have generated conflicting results, depending on the assumptions made. Here, we analyze the conditions under which selection favors the evolution of assortative mating, thereby reducing gene flow betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
262
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(275 citation statements)
references
References 57 publications
7
262
2
4
Order By: Relevance
“…In other words, the evolution of choosiness in this model may have two stable equilibria: an intermediate equilibrium with partial isolation and a high equilibrium with complete isolation. These results were later confirmed by Pennings et al (2008), Otto et al (2008), and Ripa (2009), who showed that the bistability is a consequence of positively frequency-dependent sexual selection. For small mutational step sizes, the intermediate equilibrium forms a barrier against speciation.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…In other words, the evolution of choosiness in this model may have two stable equilibria: an intermediate equilibrium with partial isolation and a high equilibrium with complete isolation. These results were later confirmed by Pennings et al (2008), Otto et al (2008), and Ripa (2009), who showed that the bistability is a consequence of positively frequency-dependent sexual selection. For small mutational step sizes, the intermediate equilibrium forms a barrier against speciation.…”
Section: Introductionmentioning
confidence: 61%
“…Our main results are that speciation is easiest if choosiness can evolve through a single large mutational step and that additional ecological loci enlarge the number of evolutionary outcomes. Compared to models with one ecological locus and infinitesimal mutations for the mating trait (Pennings et al, 2008;Kopp and Hermisson, 2008;Otto et al, 2008;de Cara et al, 2008;Ripa, 2009), both effects increase the range of parameters where speciation is possible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations